2018
DOI: 10.3390/catal8060234
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of an Antarctic Pseudomonas AMS8 Lipase for Low Temperature Ethyl Hexanoate Synthesis

Abstract: The demand for synthetic flavor ester is high, especially in the food, beverage, and cosmetic and pharmaceutical industries. It is derived from the reaction between a short-chain fatty acid and alcohol. Lipases from Antarctic bacteria have gained huge interest in the industry due to its ability react at low temperatures. The use of immobilization enzymes is one of the methods that can improve the stability of the enzyme. The current work encompasses the low temperature enzymatic synthesis of ethyl hexanoate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 58 publications
1
17
1
Order By: Relevance
“…These findings were consistent with previous studies, where lower fermentation temperature had a positive effect on lipase production (Anasontzis et al, 2014) Among the tested range of temperature (15–35°C), the optimum temperature for cold-active lipase production by Pichia lynferdii NRRL Y-7723 was 20°C as previously reported (Park et al, 2013). The effect of temperature on enzyme activity is attributed to its effect on stability, rate of the reaction, substrate solubility as well as direct influence on esterification reaction (Musa et al, 2018). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with previous studies, where lower fermentation temperature had a positive effect on lipase production (Anasontzis et al, 2014) Among the tested range of temperature (15–35°C), the optimum temperature for cold-active lipase production by Pichia lynferdii NRRL Y-7723 was 20°C as previously reported (Park et al, 2013). The effect of temperature on enzyme activity is attributed to its effect on stability, rate of the reaction, substrate solubility as well as direct influence on esterification reaction (Musa et al, 2018). …”
Section: Resultsmentioning
confidence: 99%
“…The productivity obtained by the immobilized cells on sponge was considerably higher than the free cells. A comparative study indicated that the dramatic variation and the efficiency of an immobilization process rely on the support used (Musa et al, 2018). Thus, cells adsorbed on sponge (Figure 8C) were chosen to complete the study, when these immobilized cells were reused for five successive cycles.…”
Section: Resultsmentioning
confidence: 99%
“…This yield was higher than reactions without organic solvents (35%). This means, the conversion percentage of ethyl hexanoate was significantly improved in the presence of toluene compared to other organic solvents and solvent-free system [ 52 ]. Our views in improving the esterification yield is by achieving higher solvent-accessibility via lid 1 surface engineering.…”
Section: Discussionmentioning
confidence: 99%
“…also the present study suggest that the production of lipase at high temperature due to that temperature stimuli the secretion 23 . The study of 31 reported that the effect of temperature on enzyme activity is attributed to its effect on stability, rate of the reaction, substrate solubility as well as direct influence on esterification reaction. The results in the present study agree with 9,32 it reported the optimum incubation temperature for lipase production at 37°C of Pseudomonas gessardii and certain species of Pseudomonas.…”
Section: Determination Of Lipase Activitymentioning
confidence: 99%